(untitled) (Revista Contexto & Saúde, 2025)
Objective: To evaluate the accuracy of Bedside PEWS in determining clinical deterioration in pediatric patients upon admission. Method: Cross-sectional and retrospective study. A sample of 591 medical records of children admitted to a pediatric emergency department between January and December 2018. Data were analyzed using descriptive and inferential statistics. For each Bedside PEWS cutoff point, sensitivity and specificity were estimated, using transfer to intensive care as the outcome. A Receiver Operating Characteristic (ROC) curve was constructed based on these values. Results: Upon emergency admission, for PEWS >4, the ROC curve accuracy was 76.9%, with a sensitivity of 59.1% and specificity of 78.0% (p<0.001). Upon transfer from the emergency department, for PEWS >5, the ROC curve accuracy was 87.4%, with a sensitivity of 72.6% and specificity of 94.3% (p<0.001). Conclusions: Bedside PEWS is a valid tool for assessing clinical deterioration in children, with PEWS ≥5 being the most reliable indicator.